Creating a Workflow for Integrating Live-Action and CG in Low-Cost Stereoscopic Film Production - Kala, Abhishek (Auckland University of Technology, 2010)
This thesis proposes a workflow that can be effectively used to integrate CG elements into live-action stereoscopic footage, while ensuring a comfortable viewing experience for the viewer. In stereoscopic 3-D footage, each eye is presented with a slightly different image of the same scene in order to create the perception of depth. The key question explored in this research is: how do stereoscopic images affect the integration workflow of CG elements into live-action stereoscopic 3-D footage? Stereoscopic 3-D has been around since the 1800’s with the first public viewing of a stereoscopic film occurring in 1922. The recent surge in visual effects intensive stereoscopic 3-D films is attributed to advancements in digital acquisition, digital post-production and digital projection of stereoscopic films. Studios across the world are using and testing different techniques to solve problems in the visual effects film industry; currently it is a very active area of research and experimentation. The motivation for this project came from the fact that there is no documentation available for a visual effects workflow that can be effectively used by studios and visual effects artists when transitioning into stereoscopic film production. This project will provide them with a workflow that they can use to integrate CG elements into live stereoscopic footage.
Keywords: Stereoscopic; Stereo